Impact of static magnetic field exposure on Stim1 and Itpr3 expression in hepatic cells of obese mice. - Sari, Puji; Istiqomah, Rahma Nur; Yunaini, Luluk (Journal of Advanced Veterinary and Animal Research, 2025)
Objectives: This study investigates the effects of 2 mT static magnetic field (SMF) exposure for 1 h on the expression of Stim1 and Itpr3 genes in hepatic cells of obese mice. By examining these critical regulators of calcium (Ca2+) signaling and cellular metabolism, the research aims to elucidate the role of SMF in modulating molecular pathways essential for Ca2+ homeostasis and metabolic regulation in the context of obesity. Materials and Methods: Liver samples were obtained from C57BL/6J mice and preserved in RNALater. The samples were divided into two main groups: the control group, which received a standard diet, and the obese group, which was exposed to a high-fat diet. Furthermore, the obese group was stratified based on the duration of SMF exposure, including intervals of 0, 2, 7, 14, and 21 days (1 h per day with an intensity of Bmax = 2 mT). Statistical tests were conducted with a significance level of p < 0.05. Results: The research findings highlighted a noteworthy increase in the relative expression of Stim1 and Itpr3 among obese mice exposed to SMF for 7 days (obe7) and those exposed for 14 days (obe14) in comparison to the obese group without SMF exposure. Both the obe7 and obe14 groups exhibited no significant difference in relative Stim1 expression when compared to the nonobese group. However, in terms of Itpr3 expression, the obe14 group did not show a significant difference from the non-obese mouse group. The results of the correlation analysis unveiled a substantial and robust correlation between the relative expression of Stim1 and Itpm3 (r = 0.627, p < 0.001). Conclusion: These findings suggest a potential link between SMF exposure, the expression of Ca2+ regulatory genes, and the intricate pathways involved in obesity-related molecular responses. J. Adv. Vet. Anim. Res., 12(1): 231–237, March 2025 http://doi.org/10.5455/javar.2025.l890